Old but Gold: The Use of Picture Cues to Teach Writing (An Experimental Research) - Soviyah, Soviyah; Purwaningtias, Yunia (Universitas Ahmad Dahlan, 2018)
Pictures use in an educational setting fits the idiom: old but gold. There have been plenty of studies revealing how good the use of pictures in the classrooms is. Pictures have been long known to have the ability to help motivate, demonstrate, and instruct the students during a learning process. This study is a sort of complement to the phenomenon as it focuses on researching the use of pictures in a classroom. Specifically, it aims at finding out the effectiveness of the use of picture cues in teaching writing.The study belongs to experimental research involving two groups of experiment and control. The eighth-grade students of a private junior high school in Central Java Indonesia are chosen as the subject of the research during 2017/2018 academic year. Employing a sample population technique, the study involves a total number of 56 students who are equally divided into 28 students as the experimental group and 28 students as the control group. The experimental group is taught using picture cues while the control group is taught without picture cues. Pre-test and post-test are used as techniques to collect the data. As for the data analysis technique, it’s done quantitatively applying both descriptive and inferential statistics.The result of the research shows that there is a significant difference in the students’ writing ability between those taught using picture cues and those who are not. This can be seen from the difference in the mean score between them. The result of the pre-test shows that at the beginning, both experimental and control groups have slightly different ability in writing with the mean scores 51.32 and 47.86 respectively. Meanwhile, the result of the post-test indicates an obvious difference between them in which the experimental group gains 65.75 as its mean score and the control group gets 59.14. Furthermore, the application of Independent t-test calculation results in a score of 0.000, which is lower than 0.05. This means that the use of picture cues is effective. Based on these results, it can be concluded that the use of picture cues is effective to teach writing to students.